MENGELOLA KONFLIK PASANGAN - Nurhakki Nurhakki (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2017)
The couple's relationship is the interpersonal relationship of the psychological level, so the interaction of information exchange is related to the matter of privacy (affection) so that thoughts and feelings are expressed in an over disclosure. Self-disclosure at the beginning of the relationship includes general messages not revealing privacy to penetrate relationships. Entering intimate stages of eruptions and disclosure of over disclosure can lead to a connection to penetration due to conflicting differences. The presence of couples conflict is effectively managed to keep the couple alive for a happy life, because each party in a familiar partner relationship aims to minimize suffering and maximize happiness. Conflict pair can give positive effect also negative effect. Negative outcomes: weakening relationships can erode satisfaction and commitment in relationships, undermine cohesion and work performance, increase anxiety and depression, and weaken the immune system. Positive effects of conflict if managed effectively include: preventing stagnation, stimulating interest, atmosphere, and solving problems, shaping identity, and allowing for change. The significance of communication is presented as the main approach in conflict resolution. Communication skills are the most important aspect of responding to conflict effectively.